Ta'lim Maharah al-Kalaam Fi Dhu'i al-Nazhariyat al-Ijtima'iyyah al-Tsaqafiyah Li Vygotsky - Muid, Abdul; Rohman, M. Fathor (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Learning Arabic through one of the theories of second language acquisition has a positive and effective contribution in achieving supported skills. Vygotsky's socio-cultural theory is one of the theories of language acquisition that has great urgency in supporting one's abilities. This theory emphasizes that learning is not only an individual process but also as a social interaction process under the supervision and guidance of teachers. Vygotsky's sociocultural theory is one of the language learning theories recommended by linguists and psycholinguistics to be applied in the learning process especially in speaking skills learning. The aims are to improve the proficiency and accuracy of students who have different background knowledge in using Arabic. This study aims to find out how the process of speaking skills learning based on Vygotsky's socio-cultural theory and the steps and its application in the speaking skills learning process. This study uses a library approach or library research where data sources are taken from the theories in the literature. This study has contributed to the ease of a teacher to develop learning theories that will be applied in the learning process, especially speaking skills.Keywords: Speaking skills, Vygotsky?s Socio-Cultural Theory